Architecture of One Time Password with Voice Call from SIP to PSTN - Fauzi, Esa (International Journal of Psychosocial Rehabilitation, 2020)
One-Time Password (OTP) is a one-way authentication mechanism that is usually used to verify users. Generally, the media used in OTP is SMS (short text messages). But besides SMS, sound can be used as an alternative media.SIP (Session Initiate Protocol) is a protocol that can send multimedia objects, including sound. SIP can also be connected to a PSTN (public switched telephone network) through a media gateway. Therefore, this research focuses on building a system that can send OTP from SIP to PSTN.The result of this research is an API (application programming interface) developed with the REST (representative state transfer) architecture. This API can send OTP audio from SIP to PSTN. Besides it, this API has also been tested to send many OTP simultaneously at the same time.